The Implementation of the Pancasila Student Profile in Differentiated Learning for Fifth Grade at Supriyadi Elementary School, Semarang - Yuuki Chleo Pratama Setiyono; Joko Sulianto; Dini Rakhmawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research explored the application of the Pancasila Student Profile in differentiated learning for fifth-grade students at Supriyadi Elementary School in Semarang. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The results indicated that while differentiated learning successfully integrated Pancasila values and enhanced student character development, challenges related to time management, teacher preparation, and consistent value application remained. The study concluded that further teacher training and strengthening Pancasila values within differentiated learning are crucial for improving the overall educational experience and fostering students' academic success and character growth.